EDUCAR PARA OS AFETOS NA ESCOLA - Almeida, Ana (2021)
The present study falls within the scope of the Master’s degree for Qualification for Teaching in Preschool Education and Teaching of the 1st Cycle of Primary Education, and it’s centrally theme emotions and emotional management. Being emotions on the basis of how we feel and act, i tis crucial to identify, know and know how we can manage them in various situations. Thus, it was pertinent to canny out this study because the development of emotional skills may come influence the way of acting and being related to othens. For realize the study, it was central to define the following objectives: - develop na intervention project that enables students to gain a greater understanding of their emotions and how to manage them; - develop in students skills to identify various types of emotions (pleasant or unpleasant); - understand the influence of managing emotions on students’ learning. In order to meet the objectives, the Project Work Methodology was adopted, which contributed to the definition and implementation of an intervention project in a class of the 1st grade of elementary school. The research strategy, action research together with this methodology made it possible to intervening on a concrete reality where a work in the management of emotions became pressing. After the implementation of the project, it was possible to observe changes in the level of behaviour and emotional management of students, so it was concluded that the project carried out contibuted significantly to these results.